PENYELESAIAN HUKUM TERHADAP PENCEMARAN NAMA BAIK MELALUI MEDIA SOSIAL BERDASARKAN UNDANG-UNDANG INFORMASI TRANSAKSI ELEKTRONIK - Mohd. Yusuf D.M.; Ermanto; Cecep Sujapar (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
Defamation can also be interpreted as the act of someone who intentionally makes the person's good name or reputation become tarnished or bad, causing a bad view of other people towards that person who was originally good and already known by many people to be damaged or not good. again in the public eye. Defamation is included in the complaint offense case. Because a person who feels his reputation has been tarnished or tarnished because of the negative treatment of another person can file a lawsuit in a civil court and if the reporting party wins, he can ask for compensation and get it, imprisonment can also be applied to the party who committed the defamation. The formulation of the problem in this study is the Legal Settlement of Defamation Through Social Media Based on the Electronic Transaction Information Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Transaction Information. The method used is normative legal research. Based on the results of the study it is known that the legal settlement of defamation through social media is based on the Electronic Transaction Information Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Transaction Information that defamation is an act of cyber crime or cybercrime which is regulated in the Criminal Code, articles 310 to 321 and also regulated in Article 27 paragraph (3) of Law Number 11 of 2008. Defamation is an act of spreading information that is not true and is usually in the form of slander against someone who has a bad impact on that person, the person whose name is defamed can complain about this for defamation and the person who committed the defamation can be punished by imprisonment and paying a fine. Defamation is a complaint offense, because it can only be said to be defamation if someone who feels his name has been defamed reports it to the authorities.